If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2 = x + -6 Reorder the terms: -2 + 6x = x + -6 Reorder the terms: -2 + 6x = -6 + x Solving -2 + 6x = -6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2 + 6x + -1x = -6 + x + -1x Combine like terms: 6x + -1x = 5x -2 + 5x = -6 + x + -1x Combine like terms: x + -1x = 0 -2 + 5x = -6 + 0 -2 + 5x = -6 Add '2' to each side of the equation. -2 + 2 + 5x = -6 + 2 Combine like terms: -2 + 2 = 0 0 + 5x = -6 + 2 5x = -6 + 2 Combine like terms: -6 + 2 = -4 5x = -4 Divide each side by '5'. x = -0.8 Simplifying x = -0.8
| 17-6r=7 | | 36-x^4=0 | | 5x^2=-12x-6 | | 6x^2+12x=-2 | | 3k-12=4 | | 3+2m=15 | | x^2-9x-17=0 | | -4(7f+2g)-5= | | 5x^2-8=39x | | 4(7f+2g)-5= | | -15n+2=-13n-10 | | x(x+2)=8+x+4 | | x^4+6x^2+5=0 | | 2x+y=-13 | | x*x+2=8+x+4 | | 5y-7=3y+3 | | -2x-8y=-8 | | N+2=14-4 | | -4+6m= | | 2x=10x-21 | | 3y+6=24 | | -3+10=17x-4-16x | | 0.6(5x+15)=2.7-(x+3) | | 9y-14y=-22-28 | | 5y+1=4y+10 | | 80+10p=150+5p | | 11x=47+8 | | 7s^2+5s-1=0 | | 2(3m-5)+6= | | 15c^2-2c-8=0 | | 15y-60y=0 | | 3p+9=2p+14 |